Effects of Hydrogen Cyanamide Treatment in Periods of Dormancy on Budbreaking and Flowering in Japanese Pears ‘Kosui’ and ‘Hosui’ - Yoshikawa, Eiji Reonardo; Honjo, Hitoshi; Ryu Yamamoto, Robson; José Hawerroth, Fernando; Yamane, Kenji; Luiz Petri, José (Engeigaku kenkyuu, 2014)
The effects of hydrogen cyanamide on budbreaking and flowering in the potted Japanese pears ‘Kosui’ and ‘Hosui’ cultivated under field conditions were studied during 4 periods: 2007 to 08, 2009 to 10, 2010 to 11, and 2011 to 12 seasons. The plants were treated with hydrogen cyanamide after accumulating several levels of chilling, and then budbreaking and flowering were evaluated by forcing in a greenhouse maintained at 22°C. The DeVelopmental Index (DVI) model, which was calculated according to the DeVelopmental Rate (DVR) and chilling hours below 7.2°C, was employed as an index to predict the effective timing of hydrogen cyanamide treatments. The DVI1 model, described by Oya (2006) and Sugiura (1997), refers to temperatures between -6～12°C during the period of dormancy. In this study, we refer to the DVI1 as DVI(old) model. Moreover, Sugiura et al. (2003) reported that temperatures between 21～24°C during dormancy override accumulated chilling hours in periods of dormancy. We call this the DVI(new) model. The results showed that hydrogen cyanamide treatment at 400～600 hours below 7.2°C promoted the breaking bud endodormancy of ‘Kosui’ and ‘Hosui’. The greatest effect of hydrogen cyanamide on budbreaking and flowering corresponded to a DVI(new) range between 0.65 and 0.70 for both cultivars. Moreover, the results for old DVI(old) were higher than 1.03 and those for DVI(new) were higher than 0.8, i.e., the effects of the treatment became weaker. Since hours above 21°C were higher than in other seasons in 2011 (October to February), negation of the chilling might have confounded the estimation of the application timing of cyanamide. Therefore, the value of DVI(old) was over-estimated compared to DVI(new) due to the influence of the high temperature even at the same number of chilling hours. These results suggest that DVI(new) is a suitable method for hydrogen cyanamide application as a measure against global warming.